2019
DOI: 10.1111/acem.13895
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Selecting Specific Cohorts for Benchmarking and Interpretation of Emergency Department Patient Satisfaction Scores

Abstract: ObjectivesEmergency departments (EDs) patient satisfaction metrics are highly valued by hospitals, health systems, and payers, yet these metrics are challenging to analyze and interpret. Accurate interpretation involves selection of the most appropriate peer group for benchmark comparisons. We hypothesized that the selection of different benchmark peer groups would yield different interpretations of Press Ganey (PG) patient satisfaction scores.MethodsEmergency department PG summary ratings of “doctors section”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Prior literature has suggested that ED volume, hospital size, and academic versus nonacademic status may influence patient experience and ED flow. 9,14,15 Our results supported the prior literature up to 15,000 annual admissions. The reason for our observed flattening of likelihood-torecommend scores for EDs in hospitals with greater than 15,0000 admissions remained unclear.…”
Section: Secondary Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Prior literature has suggested that ED volume, hospital size, and academic versus nonacademic status may influence patient experience and ED flow. 9,14,15 Our results supported the prior literature up to 15,000 annual admissions. The reason for our observed flattening of likelihood-torecommend scores for EDs in hospitals with greater than 15,0000 admissions remained unclear.…”
Section: Secondary Resultssupporting
confidence: 91%
“…Within our study population, there appeared to have been an inflection point at approximately 15,000 annual admissions into the hospital, with progressively higher likelihood‐to‐recommend scores as annual admissions decreased from 15,000. Prior literature has suggested that ED volume, hospital size, and academic versus nonacademic status may influence patient experience and ED flow 9,14,15 . Our results supported the prior literature up to 15,000 annual admissions.…”
Section: Discussionsupporting
confidence: 89%
“…PRC uses a 23‐question Likert‐scale measurement conducted via telephone. These domains were identified with the goal of comparing proportion of top box responses in PG versus PRC surveys; peer groups were not disclosed from either company 5 . While wording was not completely identical between PG and PRC, overlap was sufficiently matched to allow comparison for 12 domains including the all‐important “likelihood to recommend” and “overall” domains (Data Supplement , available as supporting information in the online version of this paper, which is available at http://onlinelibrary.wiley.com/doi/10.1111/acem.14121/full).…”
Section: Similar Question Top Box (%) Prc %Ile Ranking Pg Peer Group mentioning
confidence: 99%
“…We have no way of knowing this with certainty or knowing who our benchmarking peers are. This information is proprietary to these companies 5 . Also of note, this is the first report examining ED PRC patient satisfaction proportion of responses in top box scores and percentile rankings.…”
Section: Similar Question Top Box (%) Prc %Ile Ranking Pg Peer Group mentioning
confidence: 99%